PEMANFAATAN SERAT SELULOSA ECENG GONDOK (Eichhornia Crassipes) SEBAGAI BAHAN BAKU PEMBUATAN KERTAS: ISOLASI DAN KARAKTERISASI - Nata, Iryanti Fatyasari; Niawati, Helda; Muizliana, Choir (Konversi, 2013)
Water hyacinth (Eichhornia crassipes) is an aquatic weeds and as water pollution which can be reduced by using its celloluse fiber as raw material for paper production. In this work, the cellulose fiber which produced from water hyacinth stems by chemical pulping method was isolated and characterized. The operating conditions for produced the highest yield of water hyacinthâs fiber by variation of NaOH concentration and cooking time were also investigated. Dry hyacinth stems on liquor/crop ratio was 7:1 (mL/g) and mixed with 1-5% (w/v) NaOH then degested in an autoclave (120 0C; 14,5 Psi) for 5, 10, 15, 30, 60 and 120 min. The operating condition which highest yield production was mixed with newspapers fiber with ratio 1:1, 2:1, 3:1 and 4:1. The NaClO 5.25% (v/v) was added into the mixture as bleaching agent, then pressed and dried as a paper. The highest water hyacinth Â fiber yield was obtained about 32.31% (2.5% Â w/v NaOH for 15 min). When mixed with newspaper fiber at loading ratio 2:1, the highest yield and density were obtained about 37.27% and 0.567 g/cm3, respectively. Base on observation by Scanning Electron Microscope (SEM), the diameter of water hyacinthâs fiber is 80-166 nm and waste newspaper fiber is Â± 56 Î¼m. In addition, in the presence of newspaper fiber in the product was increased the characteristic peaks of paper around 5.66% (cellulose I) and 8.26% (cellulose II) base on X-Ray Difraction (XRD) result.Â Keywords: Eichhornia crassipes, chemical pulping, autoclave, kertas